A Prospective Randomized Trial of Prognostic Genicular Nerve Blocks to Determine the Predictive Value for the Outcome of Cooled Radiofrequency Ablation for Chronic Knee Pain Due to Osteoarthritis. Issue 8 (28th December 2017) - McCormick, Zachary L; Reddy, Rajiv; Korn, Marc; Dayanim, David; Syed, Raafay H; Bhave, Meghan; Zhukalin, Mikhail; Choxi, Sarah; Ebrahimi, Ali; Kendall, Mark C; McCarthy, Robert J; Khan, Dost; et al.
Abstract: Background and Objectives: Genicular nerve radiofrequency ablation is an effective treatment for patients with chronic pain due to knee osteoarthritis; however, little is known about factors that predict procedure success. The current study evaluated the utility of genicular nerve blocks to predict the outcome of genicular nerve cooled radiofrequency ablation (cRFA) in patients with osteoarthritis. Methods: This randomized comparative trial included patients with chronic knee pain due to osteoarthritis. Participants were randomized to receive a genicular nerve block or no block prior to cRFA. Patients receiving a prognostic block that demonstrated ≥50% pain relief for six hours received cRFA. The primary outcome was the proportion of participants with ≥50% reduction in knee pain at six months. Results: Twenty-nine participants (36 knees) had cRFA following a prognostic block, and 25 patients (35 knees) had cRFA without a block. Seventeen participants (58.6%) in the prognostic block group and 16 (64.0%) in the no block group had ≥50% pain relief at six months ( P = 0.34). A 15-point decrease in the Western Ontario and McMaster Universities Osteoarthritis Index at six months was present in 17 of 29 (55.2%) in the prognostic block group and 15 of 25 (60%) in the no block group ( P = 0.36). Conclusions: This study demonstrated clinically meaningful improvements in pain and physical function up to six months following cRFA. A prognostic genicular nerve block using a local anesthetic volume of 1 mL at each injection site and a threshold of ≥ 50% pain relief for subsequent cRFA eligibility did not improve the rate of treatment success.